PERCEPÇÃO DE SUPORTE SOCIAL E BEM-ESTAR NO TRABALHO: UM ESTUDO COM PROFESSORES - Ferraz, Carlos Renato Andrade (2009)
Studies on the working conditions of education professionals have always had to identify negative factors, such as burnout and stress. But it is known that variables related to interpersonal relationships can provide improved well-being in the workplace in these professionals. The teacher, the protagonist of the teachinglearning can provide well-being in the workplace and play better if your letter perception of support from those who make up their social network within your school. This paper aims to analyze the relationship between well-being in the workplace and perception of social support at work in elementary school teachers. The study included 209 teachers, elementary school in public schools and state schools, all female with mean age of 41.55 years (SD = 8.64) and the minimum level of education corresponding to the school. These teachers completed a questionnaire containing self apply four measures: Range of Work Involvement Scale, Satisfaction with Work Scale of Affective Organizational Commitment Scale and Perceived Social Support at Work. Calculated the mean, standard deviations, correlations and seven models of linear regression between the variables of the study. The results showed that satisfaction with colleagues, with the leadership and with the tasks, but little satisfaction with pay and promotions. Teachers presented affective commitment to their schools and involvement with the work they do. It was revealed perception of social support, with a higher tendency to support the information received, then the perception of emotional support and perceived instrumental support in that order. Were proven significant and positive relationships between the dimensions of wellbeing in the workplace and perception of social support at work. Regression models revealed that the three dimensions of social support at work can positively impact the three dimensions of well-being in the workplace, with greater ability tor explain to each other. It is suggested that further studies involving perception of social support at work and well-being in the workplace with other professional groups to complement these poorly studied concepts.(AU)